Units of information on dynamic message signs: a speed pattern analysis - Snehanshu Banerjee; Mansoureh Jeihani; Nashid K. Khadem; Danny D. Brown (European Transport Research Review, 2019)
Abstract A single unit of information is an answer to any anticipated question a motorist may ask. Such questions include: “What happened? Where? What do I do?” This study, a first of its kind, analyzes the optimum number of units of information Dynamic Message Signs (DMSs) should display to influence driver speeding behavior. A 155-mi2 virtual road network of the Baltimore-Washington Parkway (MD-295) in Maryland was developed for use with a medium-fidelity driving simulator, and 65 participants took part in the study. Six scenarios featured DMSs displaying 2–7 units of information, interchangeably, and a total of 296 simulation sessions were conducted. Mean speeds are calculated over five different phases: the initial speed area, visible area, readable area, lost legibility area and post DMS area. Analysis of variance (ANOVA) and post-hoc analysis showed that participants tend to accelerate as soon as they lose sight of the DMS displaying 2–3 units of information and continue to do so after they pass the DMS. An ordinary least squares (OLS) regression analysis reveals that participants older than 55 slow down the most when they encounter DMSs with 6–7 units of information. Participants in the age group of 26–35 tend to increase speeds, especially when a DMS displays 2–4 units of information. This suggests that the comprehension time is low when there are fewer units of information on a DMS. Too little information may be unclear or ambiguous whereas too much may be hard to comprehend and cause drivers to slow down.